THU0206 Influence of the Tapering Strategy TNF Inhibitors on the Immunogenicity in a Cohort of Spondyloarthritis Patients in Low Disease Activity. (9th June 2015) - Monjo Henry, I.; Plasencia, C.; Pascual-Salcedo, D.; Paredes, B.; Pieren, A.; Tornero, C.; Moral, E.; Bonilla, G.; Nuño, L.; Peiteado, D.; Villalba, A.; Jurado, T.; et al.
Abstract : Background: In spondyloarthritis (SpA) patients in low disease activity (LDA) treated with biologics it is possible to decrease dose or increase the interval of administration (tapering strategy: TS) It is hypothesized whether the use of the TS could increase the development of anti-drug antibodies (ADA) with the consequent secondary inefficacy. Objectives: To analyze the influence of the TS of TNF inhibitors (TNFi) in a cohort of SpA patients at least in LDA on the clinical activity (Bath Ankylosing Spondylitis Disease Activity Index: BASDAI and incidence of flares) and serum drug and ADA levels. Methods: Retrospective observational study of a cohort of SpA patients under TNFi: Infliximab (Ifx), Adalimumab (Ada), Etanercept (Etn) and Golimumab (Gol)] on a TS. Sixty two out of 148 SpA patients under TS treated with the first anti-TNF were included. All included patients had to be at least 6 months in LDA (defined by BASDAI <4 plus one of the following items: normal C-reactive protein (CRP) or Delta-BASDAI ≥2). Flare was defined as BASDAI ≥4 associated with elevated CRP (>5mg/L) and/or Delta-BASDAI ≥2. Clinical activity (BASDAI and Ankylosing Spondylitis Disease Activity Score (ASDAS), serological data of disease activity (CRP) were measured at baseline, prior starting the TS (pre-visit) and last visit available in the first 2 years after TS (final-visit). Results: 62 patients: 44 males (71%) and 82.2% of patients were HLA B27 positive. the subtypes of SpA are shown in the tables . No differences in clinical activity by ASDAS (p=0.219), BASDAI (p=0.271) or CRP levels (0.051) were detected between pre-visit and final-visit (see tables ). Nine (14.52%) patients were ADA positive: 5 with Ifx, 3 with Ada and 1 with Gol. Two patients were already ADA positive in the pre-visit and 7 were ADA positive at final-visit. During follow-up only 8 patients (12.9%) experienced a flare and 80% recovered the LDA after shortening the interval of administration. Patients without detectable drug levels at flare visit, developed ADA at the end of follow up (p=0.035), reaching statistical significance. None ADA positive results were found in patients with use of concomitant methotrexate (MTX) at baseline. Conclusions: In SpA patients in LDA, the tapering strategy of TNFi seems to be feasible in most patients without a relevant clinical worsening and with a low incidence of flares. Monitoring drug and ADA levels could help to predict patients with flares. Furthermore, the use of concomitant MTX seem to have a protective effect on ADA development. Disclosure of Interest: I. Monjo Henry Grant/research support from: This study has received unrestricted grants from Pfizer, C. Plasencia: None declared, D. Pascual-Salcedo: None declared, B. Paredes: None declared, A. Pieren: None declared, C. Tornero: None declared, E. Moral: None declared, G. Bonilla: None declared, L. Nuño: None declared, D. Peiteado: None declared, A. Villalba: None declared, T. Jurado: None declared, C. Diego: None declared, J. Díez: None declared, E. Martin Mola: None declared, A. Balsa: None declared